2016
DOI: 10.1021/acs.energyfuels.6b02130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Steam Reforming of Single- and Multicomponent Model Compounds of Biomass Fermentation for Producing Biohydrogen over Mesoporous Ni/MgO Catalyst

Abstract: Steam reforming (SR) of single model molecules (acetone, butanol, and ethanol) and a specific mixture (butanol/acetone/ethanol = 6/3/1, mass ratio) assumed as a model of biobutanol raw mixture has been researched over mesoporous Ni x /MgO catalysts (x represented nickel mole percent in Ni–Mg) at 673–873 K. The result showed reactant conversion at lower temperatures allowed ranking the three single-molecule compounds as the function of SR activity as follows: ethanol > acetone > butanol. The catalytic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…S6), confirming the lack of NiO [45,54], in agreement with the XAS results. The main reduction peak centered at 670 °C (Region 2) suggested that the nickel atoms were located on the surface or in subsurface layers associated with MgO in a nonhomogeneous solid solution [45,54]. In Region 3, after 900 °C, a small H 2 consumption signal indicated the presence of some nickel atoms in the bulk material, associated with MgO in a solid solution.…”
Section: Activation Of the Samplessupporting
confidence: 89%
See 3 more Smart Citations
“…S6), confirming the lack of NiO [45,54], in agreement with the XAS results. The main reduction peak centered at 670 °C (Region 2) suggested that the nickel atoms were located on the surface or in subsurface layers associated with MgO in a nonhomogeneous solid solution [45,54]. In Region 3, after 900 °C, a small H 2 consumption signal indicated the presence of some nickel atoms in the bulk material, associated with MgO in a solid solution.…”
Section: Activation Of the Samplessupporting
confidence: 89%
“…The Ni 01 P0 sample showed no reduction below 400 °C (Region 1, Fig. S6), confirming the lack of NiO [45,54], in agreement with the XAS results. The main reduction peak centered at 670 °C (Region 2) suggested that the nickel atoms were located on the surface or in subsurface layers associated with MgO in a nonhomogeneous solid solution [45,54].…”
Section: Activation Of the Samplessupporting
confidence: 87%
See 2 more Smart Citations
“…The nickel atoms were in the form of NiMgO solid solution, being reduced above 700 °C for both samples. [12,47] For Ni 10 MgO, the nickel was completely reduced, while for the sample Ni 10 MgO-P123 prepared the nickel atoms were partially reduced. The constant consumption of H 2 in Region 3 (Figure S7), with peaks at different temperatures, indicated that various Ni species were formed because of the diffusion of nickel into the support, from the outermost layer to the subsurface layer, and then to the inner lattice.…”
Section: Analysis Of the Spent Catalystsmentioning
confidence: 99%